2014
DOI: 10.1117/1.jmi.1.1.015501
|View full text |Cite
|
Sign up to set email alerts
|

Influence of study design in receiver operating characteristics studies: sequential versus independent reading

Abstract: Abstract. Observer studies to assess new image processing devices or computer-aided diagnosis techniques are often performed, but little is known about the effect of the study design on observer performance results. We investigated the effect of the sequential and independent reading design on observer study results with respect to reader performance and their statistical power. For this we performed an observer study for the detection of lung nodules with bone-suppressed images (BSIs) compared with original c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, rather than simply comparing DS system performance to that of a radiologist, it extends these prior results by assessing workflows that more realistically approximate clinical practice. Past studies have shown mixed evidence on the effect of the tested reading methodologies on overall reader performance, but none have conducted an investigation within the context of diagnostic decision support, and their effects remain unknown [13]. Our results show a sizeable variation in performance obtained depending on which reading methodology was chosen (Table 4).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, rather than simply comparing DS system performance to that of a radiologist, it extends these prior results by assessing workflows that more realistically approximate clinical practice. Past studies have shown mixed evidence on the effect of the tested reading methodologies on overall reader performance, but none have conducted an investigation within the context of diagnostic decision support, and their effects remain unknown [13]. Our results show a sizeable variation in performance obtained depending on which reading methodology was chosen (Table 4).…”
Section: Discussionmentioning
confidence: 66%
“…Prior research has explored the difference between sequential and independent study designs and their respective effects on performance [1316]. These studies have suggested that both designs produce similar performance results within comparative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In the second phase (probe), we sought to understand users' information needs while making a decision with an AI Assistant. Participants diagnosed a prostate case with the aid of an AI Assistant: in line with sequential read procedure [64], they reviewed the case immediately before the algorithmic predictions were revealed. The algorithmic predictions (benign, grade 3, grade 4, and grade 5) were displayed as visual overlays on the image (Figure 1), which the pathologists could consider when making a final diagnostic decision.…”
Section: Methodsmentioning
confidence: 99%